The Effects of An Active Listening Technique on The Nurses’ Empathy Abilities in Giving Nursing Services in Surabaya - Bambang Heriyanto; Intim Cahyono; Tumini Tumini (Humanistic Network for Science and Technology (HNST), 2018)
Nursing service given to a patient will be excellent if the nurse shows her empathy to the patient. The objective of this present research is to analyze the effects of the active listening technique on the nurses’ emphatic ability in giving a nursing service in the hospital Soewandhi, Surabaya. It was a quasi-experimental type with non randomized control group, pretest-posttest design. The population were all nurses in the hospital Soewandhi and the sample was taken randomly. The data were descriptively and inferentially analyzed using the Wilcoxon and Mann-WhitneyTests with the level of significance of 0.05. The results showed that the change of the total mean score in the emphatic abilities in the control group before and after the intervention was insignificant with the pvalue of 0.262. The intervention group showed a change of the total mean score in the emphatic abilities before and after the intervention with the p-value of 0.000. Meanwhile, among the control groups with intervention, a significant difference was shown with the p-value of 0.001. The nurses trained in the application of the active listening technique showed better empathy abilities than those who did not get any training. Keywords: Active listening technique, Empathy ability, Nursing service